Path Analysis for Soil Total Nitrogen in Relation to Selected Soil Properties in a Short-Term Flooding Wetland - Gao, Zhaoqin; Bai, Junhong; Ding, Qiuyi; Liu, Guihuan; Wang, Junjing; Lu, Qiongqiong; Zhao, Qingqing (Journal of Environmental Science and Engineering Technology, 2014)
Soil samples were collected in a typical short-term flooding wetland with two dominate vegetation types (i.e., Phragmites australis and Suaeda salsa) of the Yellow River Delta of China. Path analysis was applied to investigate the relationship between soil nitrogen and selected 12 soil properties. Correlation analysis showed that soil total nitrogen was significantly correlated with total carbon, nitrate nitrogen, available phosphorous, total potassium, total sulfur and soil organic matter (P <0.01). Path analysis demonstrated that total carbon, nitrate nitrogen and soil organic matter had higher direct and indirect positive effects to total nitrogen, whereas bulk density and salt exhibited higher negative effects. Additionally, available phosphorous, total potassium, total sulfur exhibited indirect effects on total nitrogen through total carbon.